SOCIALIZATION AND TRAINING IN THE PRODUCTION OF ENVIRONMENTALLY FRIENDLY UMKM PRODUCTS BASED ON HOUSEHOLD WASTE IN KOTA BANDA ACEH - Rahmat Muliana (CV. Naskah Aceh, 2023)
This community service was carried out in Banda Aceh City. This community service aims to instill an understanding of environmentally friendly MSMEs, especially about plastic waste and other household waste that can be used as raw materials for MSME products that have a selling value. The application of environmentally friendly MSMEs is expected to reduce excessive environmental pollution in residential areas, as well as increase the economic strength of women who are MSME players. The method used in this community service is counseling and training related to environmentally friendly MSMEs and the utilization of plastic waste. The result of this community service is the increased understanding of counseling and training participants in this community service on the importance of having an environmentally friendly business, as well as how to utilize plastic waste into valuable products. Participants succeeded in making several products from plastic waste and sold them in the MSME showroom managed by the Bada Aceh City Cooperative Office.